KEBERKESANAN APLIKASI MODUL PMKU DALAM MEMBANTU MEMPERTINGKATKAN KEMAHIRAN PENYELESAIAN MASALAH MATEMATIK BERAYAT (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract PMkuModule main aim is to help students develop their skill to solve linear mathematical questions other than develop their mathematical thinking through the 4 levels in META-4 strategy, model polya and Bar model technique. This quasi experimental was designed to determine the effectiveness of PMku strategy in solving the linear mathematical question and to determine the level of PMku strategy usage in classroom among a group of students. 85 form two students as the experiment group (n=43) was administered using PMku model,while the controlled variable (n=42) was conventionally administered. In the first data collection,the pre-test was administered before carry out the intervention. After 7 weeks of intervention, the post-test was carried out to see the comparison between this strategy with conventional teaching. The questionnaire for the effectiveness of PMku model application and students assessments towards PMku also used in order to get the evidence. ANCOVA analysiskawalan(F(1, 82) = 44.5, p< .05, R-squared = 0.532) indicated that the teachig methods using PMku module enhanced studentsâ performance in mathematic problem solving mathematical word learning as compared to the conventional teaching method. Overall, this research implication shows that the use of PMku is able to fix students level in solving the linear mathematical question and give them the positive perception practicallyKeywords :Approach PMku mathematical word problem solving, achievement in mathematics, quasi experimental.